Green Technology Book (Special Edition for EXPO 2025, Osaka, Japan): Energy Solutions for Climate Change in Asia and the Pacific - World Intellectual Property Organization (World Intellectual Property Organization, 2025)
This special edition of the Green Technology Book for EXPO 2025, Osaka, Japan, features 200+ examples of energy technologies and solutions from the Asia-Pacific region, dedicated to the diffusion of innovative green technologies by connecting the technology seekers and providers.